2020
DOI: 10.1021/acs.energyfuels.0c03309
|View full text |Cite
|
Sign up to set email alerts
|

Coal Structure and Its Implications for Coalbed Methane Exploitation: A Review

Abstract: Coal structure refers to the internal structural characteristics of coals including the degree of macroscopic and microscopic deformation, pore structure, and mechanical properties after various geothermal and geological stresses, which have substantial impacts on coal mining safety and coalbed methane (CBM) exploitation. The coal structure is an indicator of coal mechanical strength, which determines the petrophysical properties of CBM reservoirs and gas extraction or CBM production efficiency from coals. Coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 78 publications
0
38
0
Order By: Relevance
“…At present, a series of approaches to sort the pore structures in the coal reservoir have been put forward based on the physical adsorption property and capillary condensation theory (Song et al, 2020b;Mou et al, 2021). To better understand the effects of pore structure on gas adsorption capacity and flow capability, this work employs a combined classification for coal pore size from the International Union of Pure and Applied Chemistry (IUPAC) (Thommes et al, 2015;Wang et al, 2021a) and Hodot (Li et al, 2015;Li et al, 2020): supermicropores (<2 nm), micropores (2-10 nm), mesopores (10-50 nm), and macropores (50-100 nm).…”
Section: Experimental Samplesmentioning
confidence: 99%
“…At present, a series of approaches to sort the pore structures in the coal reservoir have been put forward based on the physical adsorption property and capillary condensation theory (Song et al, 2020b;Mou et al, 2021). To better understand the effects of pore structure on gas adsorption capacity and flow capability, this work employs a combined classification for coal pore size from the International Union of Pure and Applied Chemistry (IUPAC) (Thommes et al, 2015;Wang et al, 2021a) and Hodot (Li et al, 2015;Li et al, 2020): supermicropores (<2 nm), micropores (2-10 nm), mesopores (10-50 nm), and macropores (50-100 nm).…”
Section: Experimental Samplesmentioning
confidence: 99%
“…The occurrence states of gas in coal are mainly the adsorption state and the free state, and the principal occurrence area is the coal pore structure. The existing research shows that the adsorbed gas in coal pores can reach 80% and above [ 6 , 7 , 8 ]. Many researchers have studied the pore size distribution of coal based on experimental measurements and other methods.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increased number of studies of coal pore structure characteristics with different metamorphic degrees and structural types have been carried out, and the effects of changes in the coal macromolecular structure on the pore structure have been investigated . The main studies and review papers on coal pore research in recent years are systematically sorted, , and it is found that it is difficult to obtain complete pore development and connectivity characteristics due to the complex genetic types of coal pores, the wide range of pore size distributions, and strong heterogeneity; observation technology for pores with sizes below 10 nm must be improved. Although many methods are used to characterize coal pores, measurements of pores below 10 nm using indirect characterization methods, such as X-ray or fluid intrusion methods, remain limited. , The characterization and determination of the connectivity of multiscale pores in coal represent scientific problems in CBM geology and engineering that must be urgently addressed. Further, previous reviews have mainly focused on the lithological development characteristics of coal samples with different coal ranks and types, the relationship between coal seams and CBM development, and the application of the pore measurement methods (Table ), , resulting in a lack of comprehensive sorting and summary of coal pore-related factors.…”
Section: Introductionmentioning
confidence: 99%